Edukasi Cinta Bangga Paham Rupiah Di Negeri Leahari - D. Hukubun, Ronald; Tomasoa, Matheos; N. Satumalay, Vilsigelint; Sanduan, Fitria; Krisye, Krisye; N. M. Fendjalang, Sophia; V. T. Soukotta, Imanuel (Universitas Gajah Putih, Indonesia, 2023)
Rupiah is the official currency of Indonesia and is widely accepted in economic transactions within the country's borders. The rupiah can be weakened by the use of foreign currencies, the circulation of counterfeit money, and poor handling of money. To promote the importance of the rupiah, the Student Community Service (KKN) from Pattimura University in Ambon organized a program called Love Proud Understanding Rupiah. The socialization event took place at the Leahari State Office and involved preparing educational materials about the value of love, pride, and understanding of the rupiah. On May 23, 2023, the outreach program was carried out in Negeri Leahari to educate people about the significance of preserving and caring for the rupiah currency. By raising awareness about the importance of the rupiah, the socialization activities aimed to maintain the economic stability of Indonesia.